Climate smart agriculture systems : shadehouse production manual - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
Crop production, which is vital to global food security, is being affected by climate change all over the world. However, the impact is being felt more severely in the more impoverished communities. It has been predicted that over the next decades, billions of people, especially those living in developing countries, will face shortages of water and food, as well as greater risks to health and life because of climate change. With fewer social, technological and fnancial resources for adapting to changing conditions, developing countries are the most vulnerable to the impacts of climate change (UNFCCC, 2007). The IICA Delegation in Guyana has introduced a number of alternative methods that seek to improve the overall effciency, resilience, adaptive capacity and mitigation potential of production systems throughout the regions. One such system to be noted is “Protected Agriculture” which is supported by effcient water harvesting and usage.